A Non-line-of-Sight Propagation Identification Algorithm in Wireless Sensor Network. Issue 1 (April 2020) - Chu, H; Ji, P; Lian, S; Yang, H; Wu, R
Abstract: With the rapid developing of communication technology, Wireless Sensor Network(WSN) has been applied in many fields. The accuracy of localization is the vital key to all these applications. In order to mitigate the non-line of-sight(NLOS) influence, we propose a propagation identification algorithm based on Anderson-Darling(AD) test. Firstly, the status of signal is determined by the AD testing. Secondly, the particle swarm optimization algorithm is adopted to estimate the mobile node based on the identification results. Finally, the effectiveness of the algorithm is verified by simulation experiments.